The application of an Integrated Control on Eggplant for the Greenhouse Whitefly, Triαleurodes vαporαriorum - Abdallah, Safel Dawla; Michelakis, S. (ENTOMOLOGIA HELLENICA, 1992)
Integrated control of the greenhouse whitefly on eggplant, using physical (traps), chemical and biological methods, was tested. The mort efficient combination was the use of Quinomethionate and traps. Applaud and Actellic mixture was fairly effective in controlling the greenhouse whitefly. Biological control by the parasite Encarsia formosa (Gahan), resulted in moderate, but adequate control when combined with traps. Traps clone gave reasonable results. All treatments were effective in reducing whitefly population to a satisfactory low level, when compared to the untreated populations. Parasitoid/host release ratio play an important rote in the results of biological control using E. formosa. The higher relcase ratio of 4:1, parasitoid:host, gave the maximum parasitization percentage.